The Effect of High-Dose Insulin Analog Initiation Therapy on Lipid Peroxidation Products and Oxidative Stress Markers in Type 2 Diabetic Patients. (16th March 2013) - Tuzcu, Hazal; Aslan, Ibrahim; Aslan, Mutay
Abstract : Effect of high-dose insulin analog initiation therapy was evaluated on lipid peroxidation and oxidative stress markers in type 2 diabetes mellitus (T2DM). Twenty-four T2DM patients with HbA1c levels above 10% despite ongoing therapy with sulphonylurea and metformin were selected. Former treatment regimen was continued for the first day followed by substitution of sulphonylurea therapy with different insulin analogs. Glycemic profiles were determined over 72 hours by Continuous Glucose Monitoring System (CGMS), and blood/urine samples were collected at 24 and 72 hours. Insulin analog plus metformin treatment significantly reduced glucose variability. Plasma and urine lipid peroxidation were markedly decreased following insulin analog plus metformin treatment. No correlation existed between glucose variability and levels of plasma and urine oxidative stress markers. Likewise, changes in mean blood glucose from baseline to end point showed no significant correlation with changes in markers of oxidative stress. On the contrary, decreased levels of oxidative stress markers following treatment with insulin analogs were significantly correlated with mean blood glucose levels. In conclusion, insulin plus metformin resulted in a significant reduction in oxidative stress markers compared with oral hypoglycemic agents alone. Data from this study suggests that insulin analogs irrespective of changes in blood glucose exert inhibitory effects on free radical formation.